2019
DOI: 10.1111/tpj.14613
|View full text |Cite
|
Sign up to set email alerts
|

The cloning and characterization of hypersensitive to salt stress mutant, affected in quinolinate synthase, highlights the involvement of NAD in stress‐induced accumulation of ABA and proline

Abstract: Nicotinamide adenine dinucleotide (NAD), a ubiquitous coenzyme, is required for many physiological reactions and processes. However, it remains largely unknown how NAD affects plant response to salt stress. We isolated a salt-sensitive mutant named hypersensitive to salt stress (hss) from an ethyl methanesulfonate-induced mutation population. A point mutation was identified by MutMap in the encoding region of Quinolinate Synthase (QS) gene required for the de novo synthesis of NAD. This point mutation caused a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 79 publications
2
28
0
Order By: Relevance
“…Furthermore, unbalanced NAD + levels have been previously linked to increased ROS production rates and oxidative stress (Chai et al ., 2006; Katoh et al ., 2006; Schippers et al ., 2008; Luo et al ., 2019). Given the upregulation of the ROS marker transcript At ZAT12 (Xu et al ., 2017) in the mutant lines (Figure S3), and the role of NAD + homeostasis in plant abiotic stress tolerance (Hong et al ., 2020; Wei et al ., 2020), we suggest that NAD + transporter mutants may be suffering from increased oxidative stress and/or deregulated RBOH‐mediated signaling.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Furthermore, unbalanced NAD + levels have been previously linked to increased ROS production rates and oxidative stress (Chai et al ., 2006; Katoh et al ., 2006; Schippers et al ., 2008; Luo et al ., 2019). Given the upregulation of the ROS marker transcript At ZAT12 (Xu et al ., 2017) in the mutant lines (Figure S3), and the role of NAD + homeostasis in plant abiotic stress tolerance (Hong et al ., 2020; Wei et al ., 2020), we suggest that NAD + transporter mutants may be suffering from increased oxidative stress and/or deregulated RBOH‐mediated signaling.…”
Section: Discussionmentioning
confidence: 89%
“…A recent functional characterization of NDT1 and NDT2 mutants had shown reduced seed germination, a phenotype previously explained by possible enhanced ABA levels and/or signaling (de Souza Chaves et al ., 2019; Feitosa‐Araujo et al ., 2020). Furthermore, NAD(P)(H) homeostasis has previously been associated with ABA biosynthesis and signaling (Hunt and Gray, 2009a; Arias et al ., 2018; Wei et al ., 2020; Hong et al ., 2020). Taken together, these observations raised the hypothesis that altered subcellular NAD + compartmentation may trigger changes in ABA metabolism, which in turn represses entry into the stomatal lineage.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results strongly support that the deficiency of NAD is responsible for the ABA-hypersensitivity of qs-2. It was recently reported that NAD is involved in plant response to salt stress by increasing stress-induced ABA accumulation [42]. We determined the ABA contents in the wild-type and qs-2 mutant under normal growth conditions.…”
Section: Plos Geneticsmentioning
confidence: 99%
“…The old5 mutation in QS enzyme in the de novo NAD biosynthesis pathway decreases the Cys desulfurase activity of the QS enzyme and increases the steady state levels of NAD, which coincides with increased expression of oxidative stress marker genes and an early onset of senescence [41]. A recent report suggested that NAD is required for the biosynthesis of ABA and proline and plant response to salt stress [42]. However, the role of NAD synthesis in plant response to ABA has remained largely unknown.…”
Section: Introductionmentioning
confidence: 99%